Hélène Berr Journal: A Journal of Sacrifice and Struggle (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyzes the journal of Hélène Berr (Hélène Berr Journal, 1942-1944, Paris, 2008) – a Parisian Jew, and a student at the Sorbonne – which she wrote during two years of war, as a testimony of the conflicted feelings of despair, fear and hope, and her transitions from a helpless victim to a sublime author. The journal starts with a dedication from the book she received from Paul Valéry, and then it continues with quotes from Keats, Gide, Shakespeare, Conrad, Lewis Carroll; notes on the music of Bach and Chopin, the English syntax. This intertextual and palimpsestic text maps subtle steps of growth with the numerous titles it mentions (which are given in a separate list at the end of the edition), quotes, references to musical and artistic works; it maps the road of unearthing the necessity of action lead by cognition – and the determined sacrifices – of the necessity of struggle which will ensure ”the triumph of the desire for happiness over the consciousness of the imminent tragedy” (Modiano). The talented 23-year-old author describes thoroughly and emotionally her personal and family life in Paris under occupation, the growing nacism and antisemitism, working in a Jewish community, but also the intellectual and spiritual world of escape into art and writing. Her worlds are the images of life from both sides of the mirror (Carroll’s Through the Looking-Glass was one of her favorite books), where we can notice the intertwining of the portrait of the obedient victim who will be destroyed and the portrait of the disobedient author who triumphs through her own records and thoughts.
Keywords: diary; palimpsest; Holocaust; knjiženstvo; transtextuality